3D printing of self-healing ferrogel prepared from glycol chitosan, oxidized hyaluronate, and iron oxide nanoparticles. (1st October 2020) - Ko, Eun Seok; Kim, Choonggu; Choi, Youngtae; Lee, Kuen Yong
Highlights: GC/OHA/SPION ferrogel displays self-healing capability. Composition and concentration of each component regulate self-healing capability. Self-healing ferrogel can be used to form 3D-printed constructs by extrusion printing. The 3D-constructs have potential application in 4D printing. Abstract: Hydrogel systems that show self-healing ability after mechanical damage are receiving increasing attention. However, self-healing hydrogels suitable for biomedical applications are limited owing to complex preparation methods. Furthermore, few studies have demonstrated the self-healing property of ferrogels. In this study, we demonstrated that glycol chitosan (GC) and oxidized hyaluronate (OHA) can be used to form a self-healing ferrogel in the presence of superparamagnetic iron oxide nanoparticles (SPIONs) without additional chemical cross-linkers. The overall characteristics of GC/OHA/SPION ferrogel varied based on the GC/OHA ratio, SPION content, and total polymer concentration. Interestingly, GC/OHA/SPION ferrogel was used to fabricate 3D-printed constructs of various shapes via an extrusion printing method. These constructs were responsive to the magnetic field, suggesting their potential application in 4D printing. This approach to developing self-healing ferrogels with biocompatible polysaccharides may prove useful in designing and fabricating drug delivery systems and tissue engineering scaffolds, via 3D printing.